Reclaiming supremacy, negotiating modernity: Islamism and post-Islamism in post-Suharto Indonesian novels - Sudibyo; Andalas, Eggy Fajar; Taufiqurrohman, Muhammad (LITERA, 2025)
Suppressed during the New Order, Indonesian Islamic literature often used Sufi symbols. Explicit Islamic expression flourished post-1998, transforming Muslim life by merging religion and entertainment. Employing qualitative method, this study analyses three post-New Order works—Jilbab Traveler, Bumi Cinta and Geni Jora—selected for their: gender-diverse authorship, commercial success, and representation of 2000–2019 Islamic-literary trends. Using close reading, the analysis identifies thematic patterns about trends in Islamic thought through textual examination of narratives/dialogue, theme codification, and critical synthesis to construct the research argument. Analysis reveals that Islamism can now be openly expressed with the emphasis of three issues: Islamic cosmopolitanism, moral agents and individual freedom. Jilbab Traveler and Bumi Cinta advocate Islamist ideas, promoting sharia enforcement—especially for Muslim minorities in non-Muslim/secular settings—and seeking to restore Islamic supremacy through exemplary protagonists. Conversely, Geni Jora reflects post-Islamist thought, emphasizing aqidah, civil rights, equality, individual freedom, and life's enjoyment.  Overall, post-New Order Islamic literature shows a greater inclination toward Islamist ideas, stressing strict sharia adherence and rejection of Western lifestyles. These works assert that Muslims must follow Sharia rigorously and resist Western influence to reclaim supremacy. While advocating religious sovereignty, they do not explicitly demand a caliphate. Some works, however, exhibit post-Islamist elements by negotiating belief with modernity, seen in celebrating individual freedom.